Inhibitory effect of Lonicera japonica flos on Streptococcus mutans biofilm and mechanism exploration through metabolomic and transcriptomic analyses - Wang, Lin; Liu, Ping; Wu, Yulun; Pei, Hairun; Cao, Xueli (Frontiers in Microbiology, 2024)
Streptococcus mutans was the primary pathogenic organism responsible for dental caries. Lonicera japonica flos (LJF) is a traditional herb in Asia and Europe and consumed as a tea beverage for thousands of years. In this work, we investigated the inhibitory effect and mechanism of LJF on biofilm formation by S. mutans. The active extracts of LJF were validated for their inhibitory activity by examining changes in surface properties such as adherence, hydrophobicity, auto-aggregation abilities, and exopolysaccharides (EPS) production, including water-soluble glucan and waterinsoluble glucan. Findings demonstrated that LJF primarily inhibited biofilm formation through the reduction of EPS production, resulting in alterations in cell surface characteristics and growth retardation in biofilm formation cycles. Integrated transcriptomic and untargeted metabolomics analyses revealed that EPS production was modulated through two-component systems (TCS), quorum sensing (QS), and phosphotransferase system (PTS) pathways under LJF stress conditions. The sensing histidine kinase VicK was identified as an important target protein, as LJF caused its dysregulated expression and blocked the sensing of autoinducer Ⅱ (AI-2). This led to the inhibition of response regulator transcriptional factors, down-regulated glycosyltransferase (Gtf) activity, and decreased production of water-insoluble glucans (WIG) and water-soluble glucans (WSG). This is the first exploration of the inhibitory effect and mechanism of LJF on S. mutans, providing a theoretical basis for the application of LJF in functional food, oral health care, and related areas.